2018
DOI: 10.1007/s10096-018-3384-6
|View full text |Cite
|
Sign up to set email alerts
|

Implications of stx loss for clinical diagnostics of Shiga toxin-producing Escherichia coli

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag GmbH Germany, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…In addition, the presence of multiple fragments of stx-coding phages may be related to the loss of phages by sub-cultivation, which has already been demonstrated [15,16,38,51]. Based on our results, we would agree with Senthakumaran et al [38] who concluded that STEC with intact prophages may be uncommon and difficult to detect. Also, using WGS these authors observed the existence of a stx-negative "in vivo" strain O145:H28 with characteristics similar to another STEC strain of the same serotype [38].…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, the presence of multiple fragments of stx-coding phages may be related to the loss of phages by sub-cultivation, which has already been demonstrated [15,16,38,51]. Based on our results, we would agree with Senthakumaran et al [38] who concluded that STEC with intact prophages may be uncommon and difficult to detect. Also, using WGS these authors observed the existence of a stx-negative "in vivo" strain O145:H28 with characteristics similar to another STEC strain of the same serotype [38].…”
Section: Plos Onesupporting
confidence: 91%
“…Environments with a high bacterial density promote transfer of phages, with phages being both gained and lost by bacterial members within this dynamic environment [50]. In addition, the presence of multiple fragments of stx-coding phages may be related to the loss of phages by sub-cultivation, which has already been demonstrated [15,16,38,51]. Based on our results, we would agree with Senthakumaran et al [38] who concluded that STEC with intact prophages may be uncommon and difficult to detect.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, it was possible to detect two samples with free Stx phage particles (3.8% of PCR-positive/culture-negative samples) in CFS but with the use of PMA-qPCR it was also possible to identify dead cells in the samples, together with free Stx particles and inducible Stx phages in two samples (3.8%) and in eight samples with inducible Stx phages (15.1%) (Figure 2b), further demonstrating the differing causes for culture negative samples. The stx1 and stx2 genes are mobile virulence factors, located on the genome of temperate bacteriophages [46][47][48][49] which are able to integrate in the E.coli genome during lysogeny, resulting in The stx1 and stx2 genes are mobile virulence factors, located on the genome of temperate bacteriophages [46][47][48][49] which are able to integrate in the E.coli genome during lysogeny, resulting in acquired ability to express the Shiga toxin [29]; however, the prophages can be induced to enter the lytic cycle producing toxin and new phage particles [50]. In this study, mitomycin C was used for the lytic cycle induction in the enriched samples resulting in an increase of number of positive samples for the plaque assay (Table 2, 35 samples).…”
Section: Discussionmentioning
confidence: 99%
“…Where reservoirs of stxencoding bacteriophage coincide with receptive serogroup backgrounds, there exists the potential for evolution of emergent STEC strains. In particular, O26 stx status is known to be dynamic, with loss and acquisition of stx phage demonstrated in vitro and in vivo(53)(54)(55)(56). Individual pat samples from two herds in our study yielded both stx-negative and positive O26 isolates, suggesting that either the source animal wason March 21, 2021 by guest http://aem.asm.org/ Downloaded from colonised by two differing O26 strains, or by the same strain from which stx genes had been lost or acquired within the gut, or during laboratory culture.…”
mentioning
confidence: 99%